The Role of Financial Performance in Mediating The Effect of Institutional Ownership, Company Size and Sales Growth on Firm Value (Jurnal Manajemen Bisnis, 2022)
This study aims to examine the role of financial performance in mediating the effect of institutional ownership, firm size, and sales growth on firm value in consumer goods industry companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample used in this study was 116 data and selected based on the purposive sampling method. Analysis of data using path analysis test with the program Eviews 10. The results proved that institutional ownership, firm size, and sales growth does not effect the firm value, while return on equity has a significant positive effect on firm value. Institutional ownership does not effect on the return on equity, firm size has a significant negative effect on return on equity, and sales growth has a positive and significant effect on return on equity. Institutional ownership and firm size does not effect the firm value with a return on equity as an intervening variable, while sales growth has a positive and significant effect on firm value with a return on equity as an intervening variable.